Optimization of Submerged Fermentation Parameters for Instant Dark Tea Production by Eurotium cristatum. Issue 5 (18th December 2015) - Lu, Hengqian; Yue, Pengxiang; Wang, Yuwan; Fu, Ruiyan; Jiang, Jun; Gao, Xueling
Abstract: In this study, green tea extracts was used as material to produce a kind of instant dark tea by E urotium cristatum via submerged fermentation. Response surface methodology was implemented with desirability function approach for optimization of fermentation parameters of instant dark tea product. The effects of inoculum size (6–12%), liquid–solid ratio (10–20 mL/g) and fermentation time (132–204 h) on mycelia dry weight, redness and turbidity of fermented tea infusion were investigated. The optimum condition was as follows: inoculum size of 9.35%, liquid–solid ratio of 14.50 mL/g and fermentation time of 169.00 h. At this optimum point, mycelia dry weight, redness and turbidity of fermented tea infusion was 0.579 g/100 mL, 41.35 and 76.96 nephelometric turbidity units, respectively. Inoculated E . cristatum by submerged fermentation changed the content of main bioactive compounds in tea extracts. The tea extracts formed the unique dark tea taste, aroma and color. Practical Application: Using waste green tea leaves as raw materials, we developed a new strategy based on submerged fermentation to process instant dark tea product by E urotium cristatum . A dark tea infusion was achieved with good taste, aroma and color at very short time and in mild manufacturing conditions compared with traditional solid state fermentation technology. Fermentation of tea extracts by E . cristatum could combine the function of tea and E . cristatum and develop a new product with more health benefits. The submerged fermentation method increases the process efficiency to achieve similar product quality, which will be a breakthrough for instant dark tea industry.